2021
DOI: 10.3390/children8020161
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity of Serbian Children in Daycare

Abstract: Background: Monitoring of physical activity within the educational institution is of great importance, primarily because of the orientation and content implemented in the daycare. This research aimed to examine the number of steps children took during their stay in daycare with regards to age, gender and the frequency of going out. Methods: The research was conducted in four daycares in the urban environment of Novi Sad (Republic of Serbia), where 231 children, aged 5 to 7, were monitored (129 boys and 102 gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 39 publications
(22 reference statements)
3
10
0
Order By: Relevance
“…In Brazil, the educational legislation does not make the presence of physical education professionals mandatory to teach the content in preschool and the recreation happens with the class teacher 67,68 . This reality reinforces the importance of the preschool space having in its physical structure parks with equipment and a patio as factors to increase the PA of preschoolers in recreation 58,62 , as recommended by some studies 20,69 .…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…In Brazil, the educational legislation does not make the presence of physical education professionals mandatory to teach the content in preschool and the recreation happens with the class teacher 67,68 . This reality reinforces the importance of the preschool space having in its physical structure parks with equipment and a patio as factors to increase the PA of preschoolers in recreation 58,62 , as recommended by some studies 20,69 .…”
Section: Discussionsupporting
confidence: 65%
“…Although previous study suggested that children's PA levels are mainly in uenced by genetic factors 11 , evidences also point out the in uence of family 12,13 , and personal factors on PA levels 14,15,16,17,18 . In this setting, sex and age were determinants of personal factors 19 and, therefore, male preschoolers, older 19 and exposed to the outdoors 20 had higher levels of PA.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations